The ideological origins of the British Empire - Armitage, David, 1965- (Ideas in context, 2000)
David Armitage makes an outstanding contribution with this history of British conceptions of empire from the 1540s to the 1740s. He sheds new light on major British political thinkers, and the relationship between Protestantism and empire, theories of property, liberty and political economy, and the emergence of the British identity. Winner of the History Today Book of the Year prize for 2000.